FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Brillianty Theodorus; Jamaludin Iskak (LPSDI Bina Patria, 2023)
The loss of public confidence in the company’s image and the company’s management due to the substantial doubt about the company’s ability to survive, so the auditor’s responsibility to give an opinion of whether the company can maintain its viability by providing going concern opinion. This research aims to investigate the factors that have the influence on the probability of issuing a going concern opinion. The variables used are profitability, liquidity, solvability, audit quality and the prior audit opinion. The research data obtained from the financial statements of the manufacturing companies listed on Indonesia Stock Exchange period 2018 – 2021 and analyzed by binary logistic regression analysis method with program SPSS 26.0. The research result found that profitability, solvability and the prior audit opinion significantly influence the probability of having a going concern opinion from the auditor. It can be concluded that a company will not have a going concern problem if it has a good profitability and (though) low solvency. In addition, an auditor as an independent party should be reliable in providing opinions related to the issue of going concern. In addition, an auditor as an independent party should be reliable in providing opinions related to the issue of going concern.